Dick Francis's Damage [large type] - Francis, Felix; Francis, Dick (Thorndike Press, 2014)
"Jeff Hinkley is an undercover investigator for the British Horseracing Authority. He secretly follows a banned racehorse trainer through the crowds at the Cheltenham Racing Festival only to witness a bloody murder taking place right in front of his eyes. Could it have something to do with the reason the trainer was banned in the first place - the administration of illegal drugs to his horses? Then many more horses test positive for prohibited stimulants and someone starts making demands or else he will completely destroy the integrity of the racing industry. Jeff is tasked with finding the perpetrator and limiting the damage to the sport but discovers that he is up against an individual who will stop at nothing to prevail. Add to that a family situation that appears to be out of control and running downhill fast, and Jeff's mental and physical wellbeing is tested to the very limit, even his life is put on the line"--